Genome-Wide Association Study of White Blood Cell Counts in Patients With Ischemic Stroke. Issue 12 (December 2019) - Torres-Aguila, Nuria P.; Carrera, Caty; Giese, Anne-Katrine; Cullell, Natalia; Muiño, Elena; Cárcel-Márquez, Jara; Gallego-Fabrega, Cristina; González-Sánchez, Jonathan; del Mar Freijo, María; Álvarez-Sabín, José; Molina, Carlos; Ribó, Marc; et al.
Abstract : Background and Purpose—: Immune cells play a key role in the first 24h poststroke (acute phase), being associated with stroke outcome. We aimed to find genetic risk factors associated with leukocyte counts during the acute phase of stroke. Methods—: Ischemic stroke patients with leukocyte counts data during the first 24h were included. Genome-wide association study and gene expression studies were performed. Results—: Our genome-wide association study, which included 2064 (Discovery) and 407 (Replication) patients, revealed a new locus (14q24.3) associated with leukocyte counts. After Joint analysis (n=2471) 5 more polymorphisms reached genome-wide significance ( P <5×10 −8 ). The 14q24.3 locus was associated with acute stroke outcome (rs112809786, P =0.036) and with ACOT1 and PTGR2 gene expression. Previous polymorphisms associated with leukocyte counts in general-population did not show any significance in our study. Conclusions—: We have found the first locus associated with leukocyte counts in ischemic stroke, also associated with acute outcome. Genetic analysis of acute endophenotypes could be useful to find the genetic factors associated with stroke outcome. Our findings suggested a different modulation of immune cells in stroke compared with healthy conditions. Abstract : Supplemental Digital Content is available in the text.